Los fundamentos jurídicos del estado constitucional de derecho que niegan facultades inherentes a la administración pública para ejercer el control difuso de las leyes - Alache Morocho, Martín Alexander (2012)
The present investigation denominated "Legal Foundations of the Constitutional State of Right that deny faculties inherent to the Public Administration to exert the diffuse control of the laws"; Seeks to study the application of the diffuse or judicial review, provided for in the Peruvian Constitution for the Judiciary, in administrative domicile, or insofar as administrative acts have effects vis-à-vis third parties or whose effects are applicable to those administered in an administrative proceeding, as To a binding precedent of the Constitutional Court. The competence or capacity of an administrative entity to apply the diffuse control in Administrative Headquarters is analyzed, on the assumption that such acts are illegal or unconstitutional in the opinion of the entity, in accordance with the substantive and procedural rules issued by the Constitutional Court. For this, a summary and comparative study of the main characteristics of diffuse control and concentrated control as models of constitutional control, as well as the faculties and characteristics of the so-called binding precedents of the Constitutional Court